MEMBACA KODE SEMIK PADA KOMIK PORNO MANHWA DI WEBSITE MANGASUSU - Mahesa Dhamar; Rakhmad Saiful Ramadhani; Moch. Ichdah Asyarin Hayau Lailin (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
This study aims to analyze the existence of semic codes through the Roland Barthes semiotic approach in Manhwa Comics. The content of the story contained in the comic relates many aspects of pornography. Pornography itself is a negative picture that can cause bad things for the audience. Researchers use qualitative descriptive methods, descriptive itself is a form of presenting data using words or sentences both orally and in writing. The results of this study indicate the existence of semic codes or connotative codes that exist in the content of Manhwa comic stories. Researchers managed to get 37 data related to semic codes or connotative codes. Semic codes obtained by researchers are expressions that refer to things that smell of sexuality or pornography.